Financial Sector Reform and Central Banking in Centrally Planned Economies. (IMF Working Papers; Working Paper, 1990)
This paper reviews key areas of central banking reform in a sample of centrally planned economies undergoing transition to market-based systems. The discussion draws mainly on the experiences of four countries, Hungary, Poland, Czechoslovakia, and China. Significant efforts have been made, or are under consideration, in all countries to develop a more efficient framework for monetary management, and to provide greater autonomy to central banks in macro stabilization policies. These objectives call for a coordinated approach to strengthening a wide range of central banking functions simultaneously, and require that a core mass of supporting financial sector reforms be implemented to ensure effective transformation and stabilization with minimal transitional costs.